Frame Head Production Process In Category 3 Frame Chassis At Pt. Prime Dual Core - Abdul Muchlis; Sandy Suryady; Aprianto Nugroho (International Journal of Science, Technology & Management, 2021)
The frame is the main component of the chassis that functions to withstand shock, pressure and vibration when operating on the road. The chassis frame is made of SS400 material which has a good level of strength to withstand static loads, the Frame Chassis formation process uses a cold working process. This writing aims to determine the production process of the Frame Head on the Frame Chassis category 3 as well as knowing the machines used in the Frame Head production process and knowing the total tonnage required for the 400 ton Stamping machine in the blanking and piercing process on the Crossmember 0101 part, from observations that have been made. it was done that to carry out the Frame Head production process on Frame Chassis category 3, through the process of forming material or forming with the blanking, piercing, and bending methods using a 300 ton to 500 ton stamping machine, then continued with the unification process using a GMAW welding machine ( Gas Metal Arc Welding), then continued with the painting process using powder coating with the dipping method for 2 minutes, and in the Crossmember 0101 forming part process using a 400 ton Stamping machine, the total tonnage of the blanking and piercing cutting force was obtained on the Crossmember 0101 part (added with backup/strippin style g force) is 470.069 Tons.